PENGUJIAN ALAT PENGOLAHAN AIR LIMBAH BERBASIS TEKNOLOGI ELECTROCOAGULATION BERTINGKAT BERBASIS IOT - Wisnu Hendri Mulyadi; Sila Wardono; Mohammad Firza, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
The increase in the amount of untreated domestic liquid waste poses a serious challenge to the environment, especially in densely populated areas. This research aims to design and test a wastewater treatment tool using electrocoagulation technology, designed in a tiered manner. The wastewater treatment process uses two levels of electrocoagulation tank processes and is organized in a staggered manner that is integrated with a PLC-based automation system and real-time water quality monitoring via ESP32. The system consists of four tiered (cascade) tanks with an automatic water transfer mechanism without a pump, and is equipped with pH, TDS, and turbidity sensors. Testing was conducted with contact times of 10, 15, and 20 minutes. The results showed a decrease in pH from 9.3 to 8.6 at 10 minutes, 8.3 at 15 minutes, and 8.1 at 20 minutes; TDS from 736 to 546 mg/L at 10 minutes, 424 mg/L at 15 minutes, and 344 mg/L at 20 minutes; and turbidity from 1959 to 1587 NTU at 20 minutes. Energy consumption ranges from 5.43–12.39 Wh, with very low operational costs (Rp7.84–Rp17.89 per cycle).. The control and monitoring system has proven capable of improving the efficiency and effectiveness of the processing.